2000
DOI: 10.1051/vetres:2000118
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of bovine WC1+ ?? T lymphocytes from peripheral blood

Abstract: -In order to isolate and characterise resting WC1 + γδ T cells from cattle, we developed a protocol for purifying these cells by negative selection from peripheral blood. The purification method included five steps: separation of mononuclear cells on lymphoprep, depletion of monocytes by adherence to plasma-coated gelatin, enriching T cells on a nylon wool column, depleting CD2 + T cells by sheep red blood cells (SRBC), and finally depleting CD4 + and CD8 + T cells by the magnetic cell sorting technique (MACS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Activated human γδ T cells may also present antigen in vitro via major histocompatibility complex class II (MHC II), classically considered a feature of professional antigen‐presenting cells (APCs) 12 . Some studies suggest that γδ T cells express CD28 and cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4) 13 and that CD86 is involved in their activation 14 . This is supported by the finding that dendritic cells (DCs), which express high levels of CD80/86 upon infection, are more potent stimulators of γδ T cells than macrophages 13,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated human γδ T cells may also present antigen in vitro via major histocompatibility complex class II (MHC II), classically considered a feature of professional antigen‐presenting cells (APCs) 12 . Some studies suggest that γδ T cells express CD28 and cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4) 13 and that CD86 is involved in their activation 14 . This is supported by the finding that dendritic cells (DCs), which express high levels of CD80/86 upon infection, are more potent stimulators of γδ T cells than macrophages 13,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that γδ T cells express CD28 and cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4) 13 and that CD86 is involved in their activation 14 . This is supported by the finding that dendritic cells (DCs), which express high levels of CD80/86 upon infection, are more potent stimulators of γδ T cells than macrophages 13,15 . However, other studies suggest that bovine γδ cells may use alternative costimulatory pathways, independent of CD28 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Results were expressed as the ratio of a-CGRP or b-CGRP mRNA to GAPDH mRNA, and the value of a-CGRP or b-CGRP expression level in the WKY group was regarded as one. Isolation and treatment of lymphocytes Peripheral lymphocytes were purified by gradient centrifugation, using the density separation medium, Lymphoprep (Sigma, Saint Louis, Missouri, USA), as reported previously [21]. Purified lymphocytes were resuspended in RPMI 1640 medium (Gibco, Carlsbad, California, USA) at a density of 1.5 Â 10 6 cells/ml.…”
Section: Measurement Of Systolic Blood Pressure In Ratsmentioning
confidence: 99%
“…CD3 + TcR + cells are λ δ-type T-lymphocytes that are commonly observed in the juvenile period [1], and it is known that levels of these lymphocytes are low from birth in infirm calves with low resistance to disease [13]. Fikri et al [5] reported that λ δ-type T-lymphocytes produce IFNλ, which promotes the cellular immune response. It is suggested that the increase in the CD3 + TcR + cells seen in the banana group is participating in the cellular immune response.…”
mentioning
confidence: 99%